2000
DOI: 10.1046/j.1440-1819.2000.00685.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalences of periodic limb movement‐like and restless legs‐like symptoms among Japanese adults

Abstract: Prevalences of periodic limb movement-like and restless legs-like symptoms among Japanese adults were investigated. The latter symptom was significantly associated with insomnia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
48
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 4 publications
3
48
1
1
Order By: Relevance
“…We selected 30 studies on the RLS prevalence in Asian populations based on predefined criteria [12][13][14][15][16][17][18][19][20][21][22][23][24][25][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]. Table 5 and Figure 1 summarize the 31 studies (including ours).…”
Section: Rls Prevalence In the Published Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…We selected 30 studies on the RLS prevalence in Asian populations based on predefined criteria [12][13][14][15][16][17][18][19][20][21][22][23][24][25][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]. Table 5 and Figure 1 summarize the 31 studies (including ours).…”
Section: Rls Prevalence In the Published Literaturementioning
confidence: 99%
“…Table 5 and Figure 1 summarize the 31 studies (including ours). In the 3 studies that defined RLS according to the presence of a key symptom, the prevalence was relatively high, ranging from 5 to 12.1% [19,36,37]. In the 6 studies in which set-of-symptoms criteria using a questionnaire were adopted, the RLS prevalence ranged from 4.5 to 9.7% [22-25, 38, 39].…”
Section: Rls Prevalence In the Published Literaturementioning
confidence: 99%
“…[3][4][5][6][7][8] RLS is either idiopathic or it occurs in association with many physical and mental conditions. [9][10][11][12] The severity varies widely, ranging from occurring only occasionally to frequently and severely with disruption of sleep.…”
mentioning
confidence: 99%
“…1 Surveys of the general population have shown that RLS is a common disorder, and has a prevalence ranging between 2.5 and 10%. 2 Standardized criteria were proposed by the International Restless Legs Study Group (IRLSSG) in 1995 3 and these were slightly modified in 2003 4 when a four-question set recommended for epidemiological surveys also was presented.…”
mentioning
confidence: 99%